EXPERIENCE IN THE USE OF PLASMAPHERESIS IN ACUTE INFLAMMATORY DEMYELINATING POLYRADICULONEUROPATHY GUILLAIN – BARRE SYNDROME IN THE PATIENT WITH CHRONIC HEPATITIS C VIRUS INFECTION AND TYPE 2 DIABETES MELLITUS - V. A. Voinov; R. A. Gapeshin; E. S. Tarabanova; A. A. Iakovlev; K. S. Karchevskii; O. V. Isaulov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Acute inflammatory demyelinating polyneuropathy Guillain – Barre syndrome (AIDP-GB) – acquired immune mediated disease with acute onset characterized by the development of peripheral tetraparesis due to immune system attack to peripheral nerves and spinal roots. This article describes the case report of AIDP-GB development in the patient with hepatitis C and type 2 diabetes mellitus. The patient was treated with course of plasmapheresis and subsequent course of intravenous immunoglobulin (IVIG) for increasing the effectiveness of therapy. During the therapy, there was a significant improvement in the condition of patient and reduction of neurological deficit, confirmed by neurological examination and electroneuromyography, immediately after treatment and in 6 months. In addition, rehabilitation measures for the patient included physical therapy, including physiotherapy and acupuncture. To sum up, the effective treatment of AIDP-GB includes pathogenic therapy (plasmapheresis, IVIG) and rehabilitation measures to facilitate the recovery of the patient and return to professional practice.